2014
DOI: 10.1590/1676-06032014006413
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal morphological variation of the vas deferens of scorpion mud turtle (Kinosternon scorpioides)

Abstract: http://dx.doi.org/10.1590/1676-06032014006413Abstract: This study aimed to characterize the morphology of the vas deferens of Kinosteron scorpioides by macroscopic and microscopic analysis. Were used 20 adult male jurará s collected at regular intervals during the year and divided into four experimental groups in the rainy and dry seasons, being processed for light microscopy, scanning electron microscopy and transmission electron microscopy. Morphometry for tubular and luminal diameters and epithelial height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
2
1
1
Order By: Relevance
“…In contrast to Viana et al (2014) and Mahfud et al (2016), who reported that the epithelium lining other reptile ductus deferens is ciliated, no cilia could be detected in the epithelium lining the ductus deferens in the male Egyptian Nile monitor lizard in the present study. Nonciliated epithelium supports the hypothesis that the main function is storage, not transportation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Viana et al (2014) and Mahfud et al (2016), who reported that the epithelium lining other reptile ductus deferens is ciliated, no cilia could be detected in the epithelium lining the ductus deferens in the male Egyptian Nile monitor lizard in the present study. Nonciliated epithelium supports the hypothesis that the main function is storage, not transportation.…”
Section: Discussioncontrasting
confidence: 99%
“…The anatomical location of the ductus deferens in relation to the ventral surface of the kidney in the male Nile monitor lizard was similar to that previously reported in other reptiles (Guerrero et al, 2004; Viana et al, 2014). In this study, two main types of cells, principal tall cells and basal cells, could be histologically identified in the ductus deferens of male Nile monitor lizards.…”
Section: Discussionsupporting
confidence: 88%
“…Foram utilizados 06 exemplares de muçuã adultos de cativeiro em jejum, sendo três machos e três fêmeas. Para eutanásia, foi utilizado o Tiopental sódico 2,5% por via intramuscular conforme protocolo (8)(9)(10)(11) . Os cortes das três regiões do estômago foram submetidos à técnica da estreptovidina-peroxidase para detecção de antígenos de enteroglucagon presente no epitélio e glândulas do estômago do muçuã.…”
Section: Methodsunclassified
“…Sento Sé 10º19'00.00" 41º50'00.00" Pereira et al (2007); Barreto et al (2010); Viana et al (2013Viana et al ( , 2014Viana et al ( , 2015; Moura et al (2014).…”
Section: Bahiamentioning
confidence: 99%